The resource curse and the role of institutions revisited - John Narh (Environment, Development and Sustainability, 2023)
Many studies have shown that natural resource abundant countries with strong institutions tend to escape the resource curse. Institutional quality has been examined using broad indices of rule of law, the rate of murder, the share of the shadow economy and provision of public goods. Nonetheless, we need to locate the specific institutional conditions under which the curse manifests since some "rule of law" countries like Nigeria and Angola are generally classified as resource cursed. In this review, I argue that managing and distributing natural resource wealth through a centralised planning strategy and lack of a binding long-term national development plan are institutional conditions that encourage government unaccountability as they do not restrict policy makers against discretionary distribution of natural resource windfall, rent seeking, clientelism and corruption which contribute to poor economic development and growth. Also, inadequate regulations on how to address the potential or actual impacts of natural resource extraction on the livelihood of local people and the environment tend to precipitate grievance-induced resource conflict.
Keywords: 330; Resource curse; Government accountability; Institutions; Natural resource conflict; Natural resource windfall; Financial development